Construction of solidary territories with an innovation perspective for social transformation within pile-dwelling populations in Ciénaga Grande de Santa Marta (CGSM) - Polo de Lobatón, Gregoria; Lobatón Polo, Daulis; Rosentielth Martinez, Jose Luis (Cooperativismo & Desarrollo, 2020)
The purpose of this article is to point out social innovation as a strategy for the declaration of solidarity territory of the palafitic populations, Nueva Venecia, Buenavista and Bocas de Cataca, belonging to the settlements of the Ciénaga Grande de Santa Marta, hereinafter, CGSM, base for the social transformation of these communities, as a result of a final assumption in the research "Innovation strategies for the offer of tourist products that aim at improving the quality of life on the way to development", was developed methodologically under the qualitative approach Interpretive type, using the participatory action research strategy, with the application of a workshop technique in interaction with the populations of these communities and the triangulation method for the reliability of the information. The results obtained determined that the practice of the social and solidarity model based on the strategy of social innovation, admit the declaration of solidarity territory, concluding that together they establish the basis for a strength of adaptation towards the social transformation of their communities.